2014
DOI: 10.1186/s40560-014-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antithrombin in preclinical and clinical applications for sepsis-associated disseminated intravascular coagulation

Abstract: Antithrombin (AT) is known as an important physiological anticoagulant. AT inactivates thrombin and multiple other coagulation factors, thereby strongly inhibiting the over-activation of the coagulation system during disseminated vascular coagulation (DIC). AT also suppresses the pro-inflammatory reactions that are promoted through protease-activated receptor-1 during sepsis. One of the unique characteristics of AT is the conformational change it undergoes when binding to heparin-like molecules. The anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 64 publications
0
31
1
2
Order By: Relevance
“…LPS treatment led to marked dysregulation of parameters of blood coagulation akin to that seen in disseminated intravascular coagulation [35]. A pro-thrombotic state was evident at 18 h post LPS with elevation of fibrinogen levels in serum [36], and decrease in levels of antithrombin [37] and protein C [38] (Fig 7, upper panel).…”
Section: Coagulopathy Fibrinolysis and Low Platelet Count And Their mentioning
confidence: 92%
“…LPS treatment led to marked dysregulation of parameters of blood coagulation akin to that seen in disseminated intravascular coagulation [35]. A pro-thrombotic state was evident at 18 h post LPS with elevation of fibrinogen levels in serum [36], and decrease in levels of antithrombin [37] and protein C [38] (Fig 7, upper panel).…”
Section: Coagulopathy Fibrinolysis and Low Platelet Count And Their mentioning
confidence: 92%
“…Although the study did not have enough power to prove with statistical significance that AT supplementation was associated with a reduction in 28-day mortality, the results did suggest that AT supplementation improved outcomes in DIC patients (28-day mortality: 13% vs. 10%, n ¼ 60, P ¼ 1.0) (16). Furthermore, several studies have indicated that AT supplementation does not increase bleeding complications in patients with sepsis-induced DIC (16)(17)(18).…”
Section: Introductionmentioning
confidence: 91%
“…As a result, although the denuded endothelial surface could be more prothrombotic, shedding heparan into the plasma itself is antithrombotic. Syndecan-4 is known as a binding site of antithrombin, and its derangement decreases the activity of antithrombin [47]. Strand et al [53] reported that the shedding of syndecan-4 promotes leukocyte recruitment after a lipopolysaccharide challenge in mice.…”
Section: Measurement Of Glycocalyx In Plasma and Urinementioning
confidence: 99%